DEVELOPMENT OF THE SOFTWARE MODULE FOR THE CALCULATION OF ELECTRICAL LOAD CENTER OF POWER FACILITY - STASIV, ANDRII; SUDOMYR, VALENTYN; SYSAK, IVAN; OROBCHUK, BOGDAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The software module for the calculation of electrical load center (ELC) of power facility is proposed in this paper. Special attention is paid to the reqirement of creating such software module for ELC determination. It is caused by the demand of quick, accurate and convenient execution of engineering calculations which in manual mode require significant time and can be accompanied by errors. Such software module is necessary as it automates calculations and eliminates routine manual work; visualizes the results, simplifying interpretation; and contributes to the optimization of power supply, reduction of energy losses, and improvement of network reliability. Three classical methods which make it possible to determinate ELC analytically are considered. The calculation of ELC by means of one of these classical methods, which is cumbersome and time-consuming, is presented. The authors propose a simplified method for ELC determination by considering each workshop not as a set of individual machines for which their coordinates are to be determined, but as a set of distribution devices (groups of consumers) to which these machines are connected. Calculations are significantly simpler and therefore take less time. The software module for ELC calculation is proposed. The program is developed using C# programming language with .NET Framework 4.7.1 environment. The graphical interface is based on Windows Forms (WinForms) - a classic technology for creating desktop applications for Windows operating system. Standard WinForms components, including DataGridView for creaating the tabular data input form, TextBox for displaying results, and MessageBox for user feedback are actively used in the project. Events (Click, EditingControlShowing, CellClick, etc.) are processed using delegates and lambda expressions, which is a common practice for C#. In order to export tabular data to Excel, the external ClosedXML library is used. It provides simple and efficient work with .xlsx format files without the need to install Microsoft Excel. The program also implements field autofill, input data type validation as well as input error processing with autofill by default. The software module has both Ukrainian and English interfaces. The proposed software module for the determination of electrical load center provides fast and accurate calculations and has convenient and intuitive interface.